The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.schres.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Real-world implementation of precision psychiatry: Transdiagnostic risk calculator for the automatic detection of individuals at-risk of psychosis

Abstract: Background Risk estimation models integrated into Electronic Health Records (EHRs) can deliver innovative approaches in psychiatry, but clinicians' endorsement and their real-world usability are unknown. This study aimed to investigate the real-world feasibility of implementing an individualised, transdiagnostic risk calculator to automatically screen EHRs and detect individuals at-risk for psychosis. Methods Feasibility implementation study encompassing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 64 publications
(60 reference statements)
0
33
0
1
Order By: Relevance
“…The current systematic review identified only one implementation study, corresponding to 0.2% of the total pool of models developed and published, which did not report data but only described the research protocol of an ongoing project 120 (the full implementation results have been published upon completion of our literature review). 121 , 122 At the moment, precision psychiatry is severely limited by a translational gap. The implementation pathways of precision psychiatry is a perilous journey, 123 complicated by obstacles related to patients (eg, making their data available or accepting the outputs of the risk calculator), clinicians (eg, adherence to the recommendations made by prediction models and communicating risks), providers (eg, confidentiality and accessibility of data and interpretability and utility of outputs), and funders and organizations (implementing an infrastructure enabling standard prediction procedures).…”
Section: Discussionmentioning
confidence: 99%
“…The current systematic review identified only one implementation study, corresponding to 0.2% of the total pool of models developed and published, which did not report data but only described the research protocol of an ongoing project 120 (the full implementation results have been published upon completion of our literature review). 121 , 122 At the moment, precision psychiatry is severely limited by a translational gap. The implementation pathways of precision psychiatry is a perilous journey, 123 complicated by obstacles related to patients (eg, making their data available or accepting the outputs of the risk calculator), clinicians (eg, adherence to the recommendations made by prediction models and communicating risks), providers (eg, confidentiality and accessibility of data and interpretability and utility of outputs), and funders and organizations (implementing an infrastructure enabling standard prediction procedures).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a systematic review has found that only about 5% of the total pool of risk prediction models published in psychiatry is externally validated, and that only 0.2% are being considered for implementation (most models may not cross the implementation threshold, as they would not improve outcomes), highlighting a profound replication and translational gap 240 . For example, across all prognostic models reviewed in Table 5, only the transdiagnostic risk calculator has been piloted for real-world implementation in clinical practice 241 .…”
Section: Implementing Stratified/personalized Prognosismentioning
confidence: 99%
“…Die Autoren schlussfolgerten, dass ein individualisiertes prognostisches Modell, das die künstliche und menschliche Intelligenz integriert, die personalisierte Prävention psychotischer Störungen bei Menschen mit Psychoserisikosyndromen oder kürzlich aufgetretenen Depressionen erleichtern könnte. Inzwischen sind auch individualisierte Onlinerisikorechner für die transdiagnostische Vorhersage von Psychosen in der psychiatrischen Versorgung verfügbar [57][58][59][60].…”
Section: Untersuchungsmethodenunclassified